2020
DOI: 10.3390/ijms21249732
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cell Adhesion Molecule 1 (CADM1) in Cutaneous Malignancies

Abstract: Cell adhesion ability is one of the components to establish cell organization and shows a great contribution to human body construction consisting of various types of cells mixture to orchestrate tissue specific function. The cell adhesion molecule 1 (CADM1) is a molecule of cell adhesion with multiple functions and has been identified as a tumor suppressor gene. CADM1 has multifunctions on the pathogenesis of malignancies, and other normal cells such as immune cells. However, little is known about the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 101 publications
0
16
0
Order By: Relevance
“…These environmental stimuli provoke epigenetic changes, which regulate the biological modification of DNA without changing the sequences and subsequently influence the degree of gene expression [98]. The importance of epigenetic modification has been observed in various cutaneous skin malignancies, such as squamous cell carcinoma [99], melanoma [100], and lymphomas [101].…”
Section: Epigenetic Modification In Liposarcomamentioning
confidence: 99%
“…These environmental stimuli provoke epigenetic changes, which regulate the biological modification of DNA without changing the sequences and subsequently influence the degree of gene expression [98]. The importance of epigenetic modification has been observed in various cutaneous skin malignancies, such as squamous cell carcinoma [99], melanoma [100], and lymphomas [101].…”
Section: Epigenetic Modification In Liposarcomamentioning
confidence: 99%
“…Furthermore, CADM1 promotes vascular endothelial cells to repair the endothelial barrier and mast cells to release cytokines. Interestingly, high CADM1 expression in Merkel cell carcinoma, adult T-cell leukemia/lymphoma (ATLL), mycosis fungoides, and Sezary syndrome is associated with poor prognosis (Magadmi et al, 2019;Sawada et al, 2020). However, this is contrary to previous studies that showed that CADM1 acts as a tumor suppressor in most solid tumors.…”
Section: Tumors In Other Systemsmentioning
confidence: 89%
“…Recent studies identified that CADM1 was closely related to the development or regulation of skin cancers [9], such as SCC [25], malignant melanoma [27], adult T-cell leukemia/lymphoma [28], mycosis fungoides [17,29], Sézary Syndrome [30], and Merkel cell carcinoma [31].…”
Section: Discussionmentioning
confidence: 99%
“…The metastatic cascade is a complex multistep process, and the role of CADM1 expression is not restricted to cell-cell adhesion. However, it might also affect the infiltration of inflammatory cell migration into the tumor [9]. Indeed, CADM1 has a potent threshold for triggering the immune responses of immune cells such as NK-cell and CD8+ T-cell [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation